Temperature Monitoring System for Egg Incubators Using Raspberry Pi3 Based on Internet of Things (IoT) - Siti Purwanti; Anita Febriani; Mardeni Mardeni; Yuda Irawan (Universitas Muhammadiyah Yogyakarta, 2021)
The incubator is made as a substitute for hatching naturally at the same time. The success of the hatch machine is largely determined by the temperature stability in the incubator. In the use of small-scale hatcheries for native chicken hatching, they are still faced with the problem of low hatchability due to one of the obstacles, namely the power outage during the hatching process. To improve the monitoring performance of egg incubators, the writer wishes to conduct research